Removal of methylene blue and phenol onto prepared activated carbon from Fox nutshell by chemical activation in batch and fixed-bed column - Kumar, Arvind; Jena, Hara Mohan (Journal of cleaner production, 2016)
Fox nutshell was used as a new precursor for the production of a high surface area activated carbon with zinc chloride activator at 600 °C activation temperature and 2.0 impregnation ratio. The Brunauer–Emmett–Teller (BET) surface area of the prepared activated carbon was 2869 m2/g with total pore, micropore and mesopore volume of 1.96, 1.68 and 0.28 cm3/g. Methylene blue and phenol were used as adsorbates for adsorption experiment onto prepared high surface area activated carbon in batch and column scale. Adsorption kinetics of methylene blue and phenol was studied by using commonly kinetic models, i.e., the pseudo-first-order model, the pseudo-second-order model, and the intraparticle diffusion model. The experimental adsorption isotherms of these adsorbates on the prepared activated carbon were analysed using three isotherm models: the Langmuir, Freundlich and Tempkin. The equilibrium adsorption (qe) of methylene blue was increased from 249.88 to 968.74 mg/g and for phenol was increased from 19.84 to 75.37 mg/g when initial concentration was enhanced from 100 mg/L to 500 mg/L. The negative values of the enthalpy change (ΔH0 = −2.93 kJ/mol for MB and −16.92 kJ/mol for phenol) indicate that the MB and phenol adsorption process onto FNAC was exothermic in nature. In column experiments, the effects of the bed height of the packing material and flow rate of methylene blue and phenol onto prepared activated carbon were studied. [Display omitted] •High surface area activated carbon (FNAC) prepared from Fox nutshell with chemical activation using ZnCl2.•Prepared activated carbon contains high BET surface area of 2869 m2/g and micropore volumes of 1.69 cm3/g.•Prepared activated carbon has been used in the adsorption of methylene blue and phenol from their aqueous solution.•Kinetic and isothermal adsorption studies of both the adsorbates are carried out.•Adsorption capacity of FNAC to methylene blue and phenol at 500 mg/L concentration are 968.74 and 75.37 mg/g, respectively.